Visible Light‐Mediated Cyclisation Reaction for the Synthesis of Highly‐Substituted Tetrahydroquinolines and Quinolines. Issue 2 (7th December 2022) - Sherborne, Grant J.; Kemmitt, Paul; Prentice, Callum; Zysman‐Colman, Eli; Smith, Andrew D.; Fallan, Charlene
Abstract: Condensation of 2‐vinylanilines and conjugated aldehydes followed by an efficient light‐mediated cyclisation selectively yields either substituted tetrahydroquinolines with typically high dr, or in the presence of an iridium photocatalyst the synthesis of quinoline derivatives is demonstrated. These atom economical processes require mild conditions, with the substrate scope demonstrating excellent site selectivity and functional group tolerance, including azaarene‐bearing substrates. A thorough experimental mechanistic investigation explores multiple pathways and the key role that imine and iminium intermediates play in the absorption of visible light to generate reactive excited states. The synthetic utility of the reactions is demonstrated on gram scale quantities in both batch and flow, alongside further manipulation of the medicinally relevant products. Abstract : A mild one‐pot condensation/light‐mediated cyclisation reaction leading to a diverse range of densely functionalised tetrahydroquinoline and quinoline products is described, proceeding via divergent electrocyclisation and photoredox pathways, respectively. Thorough exploration of the reaction substrate scope, reaction intermediates and mechanistic pathways uncovers the key driving forces for the observed reactivity and stereochemistry.